The wrong horse was bet on: the effects of argument structure versus argument adjacency on the processing of idiomatic sentences - Reimer, Laura; Smolka, Eva (Frontiers in Psychology, 2023)
Psycholinguistic research remains puzzled about the circumstances under which syntactically transformed idioms keep their figurative meaning. There is an abundance of linguistic and psycholinguistic studies that have examined which factors may determine why some idioms are more syntactically fixed than others, including transparency, compositionality, and syntactic frozenness, however, they have returned inconclusive, sometimes even conflicting, results. This is the first study to examine argument structure (i.e. the number of arguments a verb takes) and argument adjacency (i.e. the position of the critical arguments relative to the verb) and their effects on the processing of idiomatic and literal sentences in German. Our results suggest that neither the traditional models of idiom processing (according to which idioms are stored as fixed entries) nor more recent hybrid theories (which concede some compositional handling in addition to a fixed entry) adequately account for the effects of argument structure or argument adjacency. Therefore, this study challenges existing models of idiom processing. In two sentence-completion experiments, participants listened to idiomatic and literal sentences, in both active and passive voice, without the sentence-final verb. They indicated which of three visually-presented verbs best completed the sentence. We manipulated the factor argument structure within experiments and argument adjacency across experiments. In Experiment 1, passivized three-argument sentences had the critical argument adjacent to the verb while two-argument sentences had the critical argument nonadjacent to the verb, and vice versa in Experiment 2. In both experiments, voice interacted with argument structure. Active sentences – both literal and idiomatic – showed equivalent processing of two- and three-argument sentences. However, passive sentences returned contrasting effects. In Experiment 1, three-argument sentences were processed faster than two-argument sentences and vice versa in Experiment 2. This pattern corresponds to faster processing when critical arguments are adjacent than nonadjacent and points to the dominant role of argument adjacency over the number of arguments in the processing of syntactically transformed sentences. Regarding idiom processing, we conclude that the adjacency of the verb to its critical arguments determines whether passivized idioms keep their figurative meaning and present the implications of this finding for relevant models of idiom processing.